(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to analyze the influence of participatory leadership on teacher competency at SMP Negeri 4 Probolinggo City in facing the challenges of the Industrial Revolution 4.0. Using a quantitative approach with a correlational method, this study involved 50 teachers selected through purposive random sampling. The instrument, a participatory leadership questionnaire and teacher competency, were analyzed through regression and Pearson correlation. The results show a positive and significant relationship between participatory leadership and teacher competency, with a correlation value (r) of 0.72 and a coefficient of determination (R²) of 0.518. This finding indicates that participatory leadership contributes 51.8% to teacher competency development. The implications of this study emphasize the importance of the principal’s role in implementing a collaborative participatory leadership style to support teacher professional development and create a school climate that is adaptive to technological developments.